Integration of Academics in Blockchain - R. , Brindha; Trikha, Om; Velsa, Prithvi (International Journal of Psychosocial Rehabilitation, 2020)
Blockchain is a distributed record-keeping system. It stores records in the form of encrypted blocks that are linked or “chained” together. Each block has its own generated hash and the hash of the previous block, which allows for greater security. It creates a decentralized environment where the stored records as well as all the transactions concerning the records are not controlled by any one single entity but rather all of them. Any completed transaction is stored in these blocks in a permanent, immutable, and completely verifiable and transparent way. A sector where blockchain can be applied for great benefits is academics. Academics are defined as the authorities tasked with the task of imparting education in an institution. Blockchain is a rapidly growing technology that can definitely revolutionize some aspects related to academia. This paper will review some such applications as well as an implementation of a private blockchain purpose-built for a university’s grade-entering system. This blockchain will be fully functional and offer all of the facilities of a Merkle tree, which is the standard for any application.